I want to appear like a virtuous teacher: Carnivalesque reflection as an examination of practice. (September 2019) - Porath, Suzanne L.
Abstract: This nine-month interpretive case study focused on the use of collaborative reflection meetings to support two third-grade teachers during their transition from a traditional, acquisition model of literacy curriculum to a workshop model. The changes in the teachers' pedagogical and philosophical approaches to teaching and learning that needed to accompany the shift were significant. Drawing from Bakhtin's concept of a carnival sense of the world, the collaborative reflection meetings acted as a carnival square in which the teachers could fully participate in understanding their practice through freely and familiarly dialoguing about their practice. In their use of carnivalistic mésalliances and profanation, their ideological becoming was developed as the teachers reframed the authoritative discourses that previously guided their teaching. The struggle of authoring themselves was articulated in the collaborative reflection meetings which provided the opportunity to develop internally persuasive discourses about the workshop approach.